Peran Guru dalam Memasyarakatkan Pendidikan Islam Moderat: Penelitian - Alifatud Dzakiyah; Muhammad Farih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article aims to analyze the important role of teachers in popularizing moderate Islamic education through learning approaches in formal schools and religious values-based habits in Islamic boarding schools (pesantren). Teachers not only function as instructors, but also as spiritual guides who shape an inclusive and tolerant understanding of Islamic values. This study highlights the strategies and challenges faced by teachers in carrying out their roles, and emphasizes the urgency of their contribution in shaping a just and compassionate society through moderate Islamic education. This study uses a qualitative analytical approach with literature review and document analysis as the main data sources. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that teachers play a strategic role in strengthening religious moderation through role models, inclusive learning designs, and strengthening a humanistic educational culture. Formal schools have opportunities in strengthening the curriculum and social interactions across diversity, while Islamic boarding schools contribute through the role models of kiai and the Aswaja tradition that has internalized the values ​​of tawassuth, tasamuh, and tawazun. Emerging challenges include the penetration of digital extremist narratives and the uneven distribution of teacher competencies related to religious moderation pedagogy. Government support for the Religious Moderation policy provides a significant opportunity to strengthen the role of teachers in developing a generation with moderate morals and maintaining national harmony and social cohesion.